2013
DOI: 10.1523/jneurosci.2067-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Serotonin Neuron Firing Increases Aggression in Mice

Abstract: Numerous studies link decreased serotonin metabolites with increased impulsive and aggressive traits. However, although pharmacological depletion of serotonin is associated with increased aggression, interventions aimed at directly decreasing serotonin neuron activity have supported the opposite association. Furthermore, it is not clear if altered serotonin activity during development may contribute to some of the observed associations. Here, we used two pharmacogenetic approaches in transgenic mice to selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 50 publications
4
72
0
3
Order By: Relevance
“…In this way, a 2013 study on transgenic mice showed that a chronic reduction in the levels of serotonin is associated with increased aggresivity. Moreover, pharmacological intervention on serotonergic neurons, aimed to suppress the neurotransmitter discharge, resulted in increased levels of aggression [25]. These data confirmed the fact that low serotonin activity is decreasing the threshold for aggressive behaviour and supports the idea of a direct association between low serotonin levels and increased aggressiveness.…”
supporting
confidence: 71%
“…In this way, a 2013 study on transgenic mice showed that a chronic reduction in the levels of serotonin is associated with increased aggresivity. Moreover, pharmacological intervention on serotonergic neurons, aimed to suppress the neurotransmitter discharge, resulted in increased levels of aggression [25]. These data confirmed the fact that low serotonin activity is decreasing the threshold for aggressive behaviour and supports the idea of a direct association between low serotonin levels and increased aggressiveness.…”
supporting
confidence: 71%
“…Supporting the model in which 5-HT 1B receptor signaling exerts inhibitory control over aggressive behavior, male mice that lack 5-HT 1B receptors exhibit increased aggressive behavior (Brunner and Hen, 1997;Saudou et al, 1994;Zhuang et al, 1999). Finally, decreasing 5-HTergic activity during adulthood using a pharmacogenetic approach increases territorial isolationinduced aggression using the resident-intruder assay (Audero et al, 2013).…”
Section: -Ht and Aggressive Behaviormentioning
confidence: 88%
“…4i-k), were not altered in H2BGFP mice. The distinct actions of auto-and heteroreceptors 46 , and differential impact of impaired 5-HT signalling in immature and mature mood-related circuitry 47,48 together with the spatial and temporal pattern of transgenic expression, which restricts H2BGFP to areas of high heteroreceptor expression and late developmental stages, may explain the selective impact. Although it is unlikely that the disorganization of higher-order chromatin structure is a widespread feature of neuropsychiatric disorders, the overlap between the transcriptional deficits found in H2BGFP mice and some gene associations in neuropsychiatric disorders is striking.…”
Section: Discussionmentioning
confidence: 99%